Impact of Corporate Governance on Performance of Listed Land and Property companies in Sri Lanka - Thavarasasingam, H.; Ravindran, M.; Anandasayanan, S. (University of Jaffna, 2018)
The Corporate governance practices has become a more crucial issue in recent years, because of its greater significance of practicing accuracy, maintaining accountability, establishing effective internal control and regulating organizations for achieving organizational goals. The purpose of the study is to find out the impact of corporate governance on performance of listed Land and Property companies in Colombo Stock Exchange. Chosen independent variables are auditors, board size, board composition and independent directors of Remuneration Committee. Firm size was considered as a control variable in this study. The dependent variable was identified as Firm performance which was measured using Return On Asset (ROA). The Population incorporated in this study was Land and Property sector in the Colombo Stock Exchange. From which 17 firms were used as the sample out of 19 listed firms. The data were gathered from firms’ annual financial reports and Data Stream over the period of 2011 to 2016, from the CSE website. Descriptive statistics, correlation analysis, multiple linear regression analysis were used to analyse the data and examine the hypotheses by using the E-views 8 version, in this study. The findings revealed that there is a positive and significant relationship between ROA with auditors, board composition. Independent directors of Remuneration Committee and board size are insignificantly correlated with ROA. Furthermore, it was found that the control variable (firm size) was insignificant in influencing firm performance (ROA). The R2 0.236 for the model implies that 23.6 % of the changes in dependent variable are described by both independent and control variables. It is observed that the model is good fit because the prob (F -statistic) is less than 0.05.This study provides useful information for policy makers, regulators in improving the corporate governance policies in the future and also helps in increasing and understanding the relationship between corporate governance and firm’s performance.
Keywords: Corporate Governance; Board Size; Firm Performance; Return on Assets; Listed Land and Property Companies